2002
DOI: 10.1590/s0366-69132002000400005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the growth parameters on TiO2 thin films deposited using the MOCVD method

Abstract: In this work we report the synthesis of TiO 2 thin films by the Organometallic Chemical Vapor Deposition (MOCVD) method. The influence of deposition parameters used during the growth in the obtained structural characteristics was studied. Different temperatures of the organometallic bath, deposition time, temperature and type of the substrate were combined. Using Scanning Electron Microscopy associated to Electron Dispersive X-Ray Spectroscopy, Atomic Force Microscopy and X-ray Diffraction, the strong influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…As the Al 2 O 3 -TiO 2 composite films were prepared at T dep = 723-873 K, a considerable increment in the deposition rate for this temperature range could be expected. On the other hand, it was observed that Al 2 O 3 -TiO 2 composite films showed notable rough surface morphologies at T Ti prec = 333-363 K. These results are consistent with those previously reported for the deposition of titania using the TTIP precursor under similar deposition conditions [17].…”
Section: Methodssupporting
confidence: 91%
“…As the Al 2 O 3 -TiO 2 composite films were prepared at T dep = 723-873 K, a considerable increment in the deposition rate for this temperature range could be expected. On the other hand, it was observed that Al 2 O 3 -TiO 2 composite films showed notable rough surface morphologies at T Ti prec = 333-363 K. These results are consistent with those previously reported for the deposition of titania using the TTIP precursor under similar deposition conditions [17].…”
Section: Methodssupporting
confidence: 91%
“…The anatase structure is obtained at temperatures of around 300°C, which makes it more useful for industrial applications. At temperatures between 400 and 600°C, the rutile phase is also present, while at higher temperatures, only the rutile structure is present [7] . In general TiO 2 films transform from amorphous to anatase and then to rutile depending on the annealing temperature [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Sol-gel, spray pyrolysis and sputtering processes, have been practically used for depositing photocatalytic TiO 2 film. [25][26][27] However, there are several technical challenges associated with the process such as low deposition rate, the requirement of a special and costly apparatus for deposition of film and unsuitability for coating substrates with large surface areas or complex morphologies. In our current studies, an atmospheric solution precursor plasma spray (ASPPS) process has been adopted to deposit photocatalytic TiO 2 film to overcome some of these challenges.…”
Section: Introductionmentioning
confidence: 99%